Association between statin medication and hearing impairment in a national health screening cohort - So Young Kim (Nature Portfolio, 2021)
Abstract This study aimed to investigate the association of previous stain use with hearing impairment in an adult population. Data from the ≥ 40-year-old population in the Korean National Health Insurance Service Health Screening Cohort were used. The hearing impairment group was classified based on the national registry of hearing-impaired persons. Control participants were randomly selected and matched for age, sex, income, and region of residence. The number of days of statin prescription during the 2 years before the diagnosis of hearing impairment was compared between the hearing impairment group and the control group using conditional logistic regression analysis. Additional analyses were conducted according to age and sex. The number of days of previous statin use was not different between the hearing impairment group and the control group (adjusted odds ratio [aOR] = 0.94, 95% confidence interval (CI) = 0.86–1.02, P = 0.118). According to age, in the ≥ 70-year-old group, those with hearing impairment had 11% lower rates of previous statin use than those in the control group (aOR = 0.89, 95% CI = 0.80–0.99, P = 0.039). According to sex, in the male group, 12% lower rates of previous statin use were observed among those with hearing impairment than among those in the control group (aOR = 0.88, 95% CI = 0.79–0.99, P = 0.037). Previous statin use might have an effect on reducing the prevalence of hearing impairment in elderly individuals and men.